Sizing of flaws using ultrasonic bulk wave testing : a review - Felice, Maria V. (2020)
Ultrasonic testing is a non-destructive method that can be used to detect, locate and size flaws. The purpose of this paper is to review techniques that utilise ultrasonic bulk waves to size flaws. Flaws that are embedded within a component (i.e. remote from any surface) as well as flaws growing from inaccessible surfaces are considered. The different available techniques are grouped into the following categories: amplitude, temporal, imaging and inversion. The principles, applications and limitations of the different techniques are covered, as well as approaches to assessing the performance of the techniques. Finally, remaining gaps and challenges in sizing flaws, particularly in an industrial setting, are discussed.